Sustainable Energy Planning and Management with focus on local energy system transition, spatial carbon factors, community ownership, trust, and household energy management. - Østergaard, Poul Alberg; Duic, Neven (International Journal of Sustainable Energy Planning and Management, 2025)
This 46th volume of the International Journal of Sustainable Energy Planning and Management presents contemporary work within the diverse field of energy planning with important new contributions on local energy system transition and district heating transition – both scenario-based analyses applying the EnergyPLAN model. The volume also probes into spatial carbon emission factors for China. Moving towards implementation of energy transition measures, the volume includes work on community ownership models as well as trust and acceptance of geothermal projects in East Africa. Lastly, and novel to this journal, a final article addresses links between religious practise and energy management in Indonesian households.